1970
DOI: 10.1136/hrt.32.6.747
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal left heart function after operation for atrial septal defect.

Abstract: Post-operative data have been presented in seven patients with atrial septal defect. In five of them, residual patency of the atrial septum was found at cardiac catheterization, but in two the defect had been closed. All showed evidence of 'left-sided dysfunction', expressed either as an increase in the pulmonary arterial wedge pressure or the left ventricular end-diastolic pressure or both. The reasons for these findings are not clear, though in several there were indications of impaired right ventricular com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 7 publications
1
20
1
Order By: Relevance
“…All of them were asymptomatic. Their findings did not correlate with age in patients operated on after 11 years of age, contrary to the findings of Petersson [26], The causes of the impairment in cardiac performance after closure of ASD II are presumably sequelae to the longstanding hemo dynamic stress upon the right ventricle, and in some cases an additional impaired left ventricular function [11,13,16,37]. The basic abnormality might be due to a defective contractile response, and abnormal compli ance characteristics of the ventricular myocardium or a combination of the two.…”
Section: Discussioncontrasting
confidence: 56%
“…All of them were asymptomatic. Their findings did not correlate with age in patients operated on after 11 years of age, contrary to the findings of Petersson [26], The causes of the impairment in cardiac performance after closure of ASD II are presumably sequelae to the longstanding hemo dynamic stress upon the right ventricle, and in some cases an additional impaired left ventricular function [11,13,16,37]. The basic abnormality might be due to a defective contractile response, and abnormal compli ance characteristics of the ventricular myocardium or a combination of the two.…”
Section: Discussioncontrasting
confidence: 56%
“…Immediate abnormal left heart function after surgical closure of ASD has first been described as early as in 1971 by Davis et al [4]. The authors reported on 7 patients, who exhibited an increase in the pulmonary artery wedge pressure or left ventricular end-diastolic pressure or both.…”
Section: Discussionmentioning
confidence: 97%
“…Immediate postoperative or postinterventional left heart failure was mostly reported in the elderly patient [4][5][6][7]. In the present cohort, older patients needed significantly more inotropic support postoperatively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is reported that surgical closure of atrial septal defect (ASD) leading to acute left heart failure may occasionally require partial re-opening [1,2]. The characteristics of patients with worsening conditions were hypoplasia of the left ventricle and/or pulmonary artery hypertension (PAH) [1].…”
Section: Introductionmentioning
confidence: 99%